Horizontal Backward Launch Dynamics Modeling and Analysis - Liangyu Zhao; Yi Jiang; Xinlin Wei; Liqi Ma; Xiang Li (International Journal of Aerospace Engineering)
Fighters’ air strikes play a vital role in modern warfare. But, with the development of fighters, the amount of bombs will inevitably become a major disadvantage due to the limitations of the invisible design and other functions, so a combination of the old model bombers and the advanced fifth-generation fighters has been proposed. This paper takes the aircraft missile horizontal backward launch system as the research object; firstly, the finite element model of the missile’s off-track is established, and the simulation calculation under the fixed platform is tested to verify the correctness of the finite element model. Meanwhile, the simulation parameters of the initial trajectory are obtained. Then, by establishing the separation model of the machine under the open state of the aircraft’s rear launcher, the variation of the flow field during the separation process of the missile is analyzed, and the variation of the force and the attitude of the missile is studied. It is found that the pitching motion of the missile is greatly affected by the initial pitch angle, it is always in the heading state during the whole separation process, and the yaw motion is not obvious.